Selective Laser Trabeculoplasty: An Update. Issue 1 (January 2016) - Kennedy, Jeffrey B.; SooHoo, Jeffrey R.; Kahook, Malik Y.; Seibold, Leonard K.
Abstract : Abstract: Selective laser trabeculoplasty (SLT) is an effective treatment option for the reduction of intraocular pressure (IOP) in patients with ocular hypertension or open-angle glaucoma. The mechanism by which SLT lowers IOP is not completely understood and is likely multifactorial. Published studies indicate that SLT is at least as effective as argon laser trabeculoplasty or medications at lowering IOP in many forms of glaucoma. In addition to IOP reduction, SLT may decrease IOP fluctuation and can be successfully used as primary or adjunctive therapy for the management of both early and advanced glaucoma. However, SLT may not be effective in certain forms of glaucoma, and the IOP-lowering effect seems to wane with time. High pretreatment IOP is the strongest predictor of treatment success, even in patients with normal-tension glaucoma. Repeatability of SLT has been controversial, but recent evidence suggests that it can be successfully repeated to achieve additional or recurrent IOP reduction, even in eyes that only had a modest response to initial treatment. Adverse events are uncommon after SLT, and the most common complications such as discomfort and inflammation are typically mild and transient. Further investigation is required to determine the optimal treatment parameters for SLT treatment. Limited evidence suggests that SLT is cost-effective as primary therapy for patients with glaucoma.